The value of being socially responsible: A primal-dual approach - Daniela Puggioni; Spiro E. Stefanou (Banco de México, 2018)
This paper models Corporate Social Responsibility (CSR) as one of the outputs that results from a firm's decisions regarding what and how to produce. The framework developed allows for studying technical efficiency and deriving a system of internal shadow prices to quantify the value of implementing socially responsible activities. The empirical application focuses on the food and beverage manufacturing sector worldwide. The results indicate high levels of technical efficiency in this sector and document a positive average shadow price of CSR activities, implying that the net value of implementing this kind of activities is positive to the firm as their benefit exceeds the cost. In particular, it is shown that increasing the CSR engagement at the margin positively contributes to the creation of firm value, while reducing it has a negative marginal impact.
Keywords: C14; D24; M14; M20; 330; Productivity and competitiveness; Decision processes; Non-parametric technology; Shadow prices; Corporate Social Responsibility